Analysis and Design of Waste Management System Using the Spiral Model Towards Smart Cities - N. Tri Suswanto Saptadi; Phie Chyan; Andrew Christhoper Pratama (SISFORMA, 2019)
IT Governance has provided hope in human life, especially waste management and environmental cleanliness services. The role of IT becomes very important when people want services that are fast, accurate and relevant. Technology using Geographic Information Systems (GIS) has provided opportunities and made it possible to interact easily. The purpose of this research is to provide a GIS for the city environmental and sanitation services in order to provide good services in creating a clean environment. The research method uses the system analysis method with a spiral model approach in system design. The results of the design of GIS have been able to improve the performance of waste management in the city of Makassar.